MQTT essentials : a lightweight IoT protocol : the preferred IoT publish-subscribe lightweight messaging protocol /: a lightweight IoT protocol : the preferred IoT publish-subscribe lightweight messaging protocol. (2017) - Hillar, Gastón C (Gastón Carlos)
No abstract available